OLAHRAGA DAPAT MENINGKATKAN FUNGSI KOGNITIF MELALUI MODULASI EPIGENETIK EKSPRESI GEN BRAIN-DERIVED NEUROTROPHIC FACTOR (BDNF) - Wahyuni, Nila; Satria Nugraha, Made Hendra; Juhanna, Indira Vidiari (Sport and Fitness Journal; Volume 6, No.3, September 2018DO - 10.24843/spj.2018.v06.i03.p04, 2019)
ABSTRACT Exercise may improve cognitive function and slow the onset of neurodegeneration, but the underlying mechanism had not yet known certainly. The purpose of this paper is to know the mechanism of exercise in improving cognitive function in terms of biomolecular aspects. The method of this paper is literature study of articles about the benefits of exercise in improving cognitive function in terms of biomolecular aspects. Cognitive function is a function related to perception, learning process, concentration, memory and problem solving. Exercise is useful for improving cognitive function mediated by a neurotropin-brain brain-derived neurotrophic factor (BDNF). BDNF has important role in neural plasticity, nerve excitability, and especially in learning process and memory improving. Exercise can improve cognitive function by inducing increased BDNF expression that occurs through the mechanism of epigenetic regulatory change. The change in epigenetic regulation caused by exercise through DNA methylation, which increase the expression of BDNF mRNA in the hippocampus. The change in epigenetic regulation caused by exercise, which also increase the expression of BDNF mRNA is a histone modification. The increased expression of mRNA in the hippocampus is not only increase synapse plasticity in the hippocampus area but also synapse transmission, which lead to the increasing of molecules expression related to learning and memory. Keywords: Sport, Brain-derived neurotrophic factor (BDNF), Epigenetic.